THE SIGNIFICANCE OF NATIONAL AND UNIVERSAL VALUES IN SHAPING AN INDIVIDUAL’S SPIRITUAL WORLDVIEW - Umarov Hamdam Tukhxtaevich (Innovate Conferences, 2025)
This article reveals the importance of enhancing the moral and spiritual worldview of young people by fostering harmony between national and universal values in the context of complex trends such as hybrid identity and mobile consciousness emerging under the influence of the global information environment. It also analyzes, from a philosophical perspective, the youth policy and reforms implemented in the field of spiritual education in Uzbekistan and their role in ensuring socio-ideological stability. Furthermore, the paper discusses the necessity of promoting national and universal values as a conceptual foundation for developing ideological immunity among young people in the face of modern challenges.
Keywords: spiritual worldview, national values, universal values, global influence, hybrid identity, ideological immunity, youth policy, moral education, Generation Z, Generation Alpha.